Peningkatan Literasi dan Inklusi Keuangan Syariah melalui “PELITA PAGI” - Siti Afidatul Khotijah; Diah Agustina Prihastiwi; Ari Nurul Fatimah (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
The purpose of this Community Partnership Program (PKM) is to provide understanding and expertise to GP Ansor Trasan Village in Islamic financial literacy and inclusion through the use of information technology (PELITA PAGI) so that GP Ansor in Trasan Village can improve family financial capabilities. This can be directly practiced by teaching investment in sharia. Ansor youth who take part in the community as helpers, fighters, and even pioneers in broadcasting, enforcing, and fortifying Islamic teachings must also be able to adapt to the growing development of technology, including in financial management. This service is carried out by providing investment understanding and training to Ansor youth in Islamic financial literacy and inclusion. This is also done by utilizing increasingly advanced technology in the form of securities applications (AJA**), so that Ansor youth can improve the financial capabilities of families and groups. The results of the service activities, it can be concluded that the service participants who came from GP Ansor Trasan Village gained knowledge and skills about Islamic financial literacy and inclusion. In addition, participants can start practicing sharia investment through the use of information technology in the AJAIB application.